Karakteristik Fragmen Gen Penyandi Cytochrome C Oxidase Subunit I (COI) Hama Kepik Penghisap Buah Kakao (Theobroma cacao L.) - Muzuni, Muzuni (Fakultas MIPA UNM, 2018)
Abstract The purpose of this research is to know the character of partial sequences of the COI gene form fruit-sucking pest. The gene fragments were isolated using PCR (Polymerase Chain Reaction) techniques with specific primers, HlpF and HlpR. Character of gene fragments observed were fragment size, nucleotide sequence, similiarity, restriction map, and hydrophobicity. The size of the fragment was determined by electrophoresis of PCR products, similarity values were determined by aligning the nucleotide sequence of the PCR product with the nucleotides present in GenBank, the restriction map determined by the RestrictionMapper program, and the hydrophobicity profile determined by the BioEdit program. The results showed that PCR yield fragment size 552 pb. The results of alignment analysis showed that PCR fragment had similarity of 88% with Helopeltis theivora, 87% with Helopeltis antonii, 87% with Helopeltis bradyi and 84% with Pacipeltis maesarum. Based on the results of the analysis using RestrictionMapper program shows partial sequences of the COI gene form fruit-sucking pest has 25 sites of restriction enzyme cutting which is class of type II endonuclease enzyme. The results of the hydrophobicity analysis using the BioEdit program indicate that the COI protein is hydrophilic and hydrophobic which shows the integrated COI protein on the membrane.Keywords: COI gene fragment, fruit-sucking pest, PCR, Cocoa Crop